Comparative Study between Retrograde Intrarenal Surgery and Percutaneous Nephrolithotomy for the Treatment of Renal Stones - Paul, Deb Prosad; Das, Debasish; Rahman, ASM Zahidur; Habibullah, Tarafder; Akter, Sonia; Momen, Md Mahfuzul (Journal of Enam Medical College, 2019)
Background: The prevalence of urolithiasis has increased during the last decades and now affects approximately 9% of the adult population specially in developed countries. European Urology Guidelines recommend PCNL in stones larger than 2 cm in size and ESWL in stones smaller than 2 cm in size as the first treatment option. With advances in technology, new generation flexible ureteroscopes with safe and effective lithotripters such as holmium laser have been developed and RIRS became an important alternative in the treatment of large urinary stones. Objective: To evaluate the safety and efficacy of retrograde intrarenal surgery (RIRS) in the treatment of kidney stones and to compare its results with those of percutaneous nephrolithotomy (PCNL). Materials and Methods: We retrospectively analyzed a total of 50 patients ─ 27 patients (20 males and 7 females) who underwent PCNL and 23 patients (17 males and 6 females) who underwent RIRS between January 2015 and December 2017. Results: The mean duration of operation was 60.65 ± 23.56 minutes in the RIRS group and 50.55 ± 12.77 minutes in the PCNL group (p<0.047). The hospital stay was significantly shorter in the RIRS group (2.21 ± 0.9 vs 5.29 ± 1.53 days in the RIRS and PCNL groups, respectively; p<0.016). Stone-free rates after one session were 88.6% and 84.8% in the RIRS and PCNL groups respectively. Blood transfusions were required in five patients in the PCNL group. Complication rates were higher in the PCNL group. Conclusion: This study reveals that RIRS can be an alternative to PCNL in the treatment of kidney stone. J Enam Med Col 2019; 9(2): 84-89